Sequential methodology for signaling business cycle turning points - Vasyl Golosnoy; Jens Hogrefe (Kiel Institute for the World Economy (IfW), 2009)
The dates of U.S. business cycle are reported by NBER with a considerable delay, so an early notion of turning points is of particular interest. This paper proposes a novel sequential approach designed for timely signaling these turning points. A directional cumulated sum decision rule is adapted for the purpose of on-line monitoring of transitions between subsequent phases of economic activity. The introduced procedure shows a sound detection ability for business cycle peaks and troughs compared to the established dynamic factor Markov switching methodology. It exhibits a range of theoretical optimality properties for early signaling, moreover, it is transparent and easy to implement.
Keywords: C44; C50; E32; 330; Business cycle; CUSUM control chart; Dynamic Factor Markov switching models; Early signaling; NBER dating; Konjunktureller Wendepunkt; Konjunkturprognose; Prognoseverfahren; Sequentialanalyse; Statistische Qualitätskontrolle; USA